Prevalence and risk factors of hearing impairment among neonates admitted in NICU in a tertiary care centre in South India - Nair, Varsha S.; Das, Prarthana; Soundararajan, Palanisamy (International Journal of Contemporary Pediatrics, 2018)
Background: Present study was conducted to assess the prevalence of hearing impairment using measurements of Otoacoustic Emission (OAE) in newborns admitted to NICU and to determine the risk factors predictive of hearing impairment in these newborns. Methods: The study was conducted from January 2016 to June 2017 in the NICU under the Department of Pediatrics. All neonates admitted for more than 48 hours in the NICU were included. Neonates who died during the study period were excluded. All candidates underwent hearing loss in a sound treated room in the department using Distortion Product Otoacoustic Emissions (DPOAE) test at the time of discharge. Babies who failed this initial screening underwent another OAE test within 1 month after discharge, and those who failed the test again were referred to an Otologist for comprehensive audiological assessment at 3 months. Results: Of the 200 neonates included in the study, 101cases (50.5%) failed the initial screening. 1 case (0.5%) failed the second OAE screening and moderate hearing loss was diagnosed in this child using BERA. Risk factors included mechanical ventilation (p=0.01), prematurity (p=0.01), low Apgar scores (p<0.01) and multiple gestation (p<0.05). Other conditions predominating in neonates who failed hearing screening included TTN, MAS, LBW and neonatal jaundice. Conclusions: Newborn infants admitted to the NICU are at a higher risk for hearing impairment due to exposure to multiple risk factors. The two staged screening protocols with DPOAE is a useful protocol for detecting hearing loss in newborns and can be implemented as a national program.